An Assessment of the Development Potential of Manufacturing Industries in Ukraine - Ishchuk, S. O.; Sozanskyy, L. Yo. (Statistics of Ukraine, 2020)
To ensure the competitiveness in world markets in the context of deepening globalization processes, Ukraine needs to adjust its own raw material base, which will qualitatively change the structure of Ukrainian exports from raw materials to goods with a high share of value added. The purpose of the article is to assess the development potential of chemical, textile, agro-processing and woodworking industries of Ukraine on the basis of import substitution and export orientation, and to substantiate organizational and economic forms of its practical implementation. The authors propose an interpretation of the term “industrial system development potential”. The peculiarities of operation of the manufacturing industry in Ukraine are determined on the basis of a comparative assessment of the density of cross-sectoral links, the cost and innovation level of domestic and European chemical, textile, woodworking and agro-processing industries. Based on the results of the analysis of the technological profile, the level of capacity utilization and performance indicators of the largest chemical enterprises of Ukraine, the strategic guidelines for the development of promising chemical industries are substantiated and organizational and economic forms of realizing their potential are proposed, in particular in the Western region. Proposals for ensuring competitive conditions for participants in the domestic market of light industry products are provided, the need for simplified regulatory procedures and investment incentives to ensure the development of domestic light industry enterprises is substantiated. An organizational mechanism for restoring the raw material base of textile and other industries is developed. The regions of Ukraine are grouped according to the potential of timber harvesting and industrial processing. The perspective directions for the woodworking industry development in the administrative-territorial units of the Western region are defined (by production type), and the basic strategies of their realization, focused on the internal and external markets, are outlined. A comprehensive review of operation problems of agro-processing productions in Ukraine is made through the prism of their resourcing from a regional perspective. The key problems are outlined and the prospects for the development of grain, meat and milk productions are substantiated, based on current and forecasted trends in the respective commodity markets. Organizational forms for realization of the development potential of agro-processing productions in Ukraine and mechanisms for their institutional support are proposed.